Effect of Graphite Particle Size on Structural and Morphological Characteristics of Carbon Nanotubes Grown by Microwave Oven - Algadri, Natheer A.; Hassan, Z.; Ibrahim, K.; Bououdina, M. (2017)
The influence of graphite particle size on the formation and diameter of carbon nanotubes (CNTs), is investigated. graphite with different diameters are used for the growth of CNTs by a cost-effective method using a microwave oven. Morphological observations by field emission scanning electron microscopy (FESEM) reveal consistently that smaller graphite diameter generates CNTs with a different diameter. Raman spectroscopy indicates that the full width at half maximum (FWHM) of G, D and 20 bands decreases gradually with increasing CNTs diameter. Furthermore, CNTs diameter is found to be inversely proportional to (002) line width